Modulation of Morpho-Physiological Responses in Populus deltoides by Elevated Carbon Dioxide and Temperature - Yadav, Santosh Kumar; Singh, Hukum; Nautiyal, Raman; Ginwal, Harish Singh; Ansari, Shamim Akhtar; Barthwal, Santan (Forest science, 2020)
Abstract Rising atmospheric carbon dioxide (CO2) and temperature alter gene-expression arrays commensurate with physio-morphological changes, resulting in issues of adaptation, growth patterns, and productivity of terrestrial vegetation. An experiment was conducted to investigate the adaptive response of Populus deltoides clone G48 to the combined effect of elevated CO2 and temperature inside open-top chambers. The elevated CO2 and temperature acted as environmental cues to help express upregulated/downregulated genes involved in important metabolic pathways. As a result, P. deltoides exposed to the elevated CO2 and temperature developed adaptation to undo the effect by enhancing gaseous exchange, transpiration, and carbon assimilation and partitioning as observed on 180 days after treatment. The elevated conditions significantly enhanced stomatal density and size on adaxial/abaxial leaf surfaces, chlorophyll b that augmented photosynthesis, stomatal conductance, transpiration, and internal CO2, but decreased instantaneous and intrinsic water-use efficiency. These stimulated biomass accumulation in root, stem, and leaves. Hence, the elevated conditions of CO2 and temperature operate at the gene-expression level that acts pleiotropically for reinforcement of photosynthetic apparatus, morphological amendment for accelerated gaseous exchange, and finally growth and biomass improvement, supporting adaptive plasticity of clonal planting stock of the species to future climatic change and global warming.